2022
DOI: 10.3390/ijms23105640
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Steroid and Triterpenoid Metabolism in Calendula officinalis Plants and Hairy Root Cultures Exposed to Cadmium Stress

Abstract: The present study investigated the changes in the content of steroids and triterpenoids in C. officinalis hairy root cultures and plants exposed to cadmium stress. The observed effects included the content and composition of analyzed groups of compounds, particularly the proportions among individual sterols (e.g., stigmasterol-to-sitosterol ratio), their ester and glycoside conjugates. The total sterol content increased in roots (by 30%) and hairy root culture (by 44%), whereas it decreased in shoots (by 15%);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…The obtained diethyl ether extracts of hairy roots were fractionated chromatographically as described in Section 4.4 . Based on GC-MS analysis of the fraction of the free steroids, the compositions of these compounds were the same as described previously [ 27 ], i.e., the main sterols identified in this fraction were campesterol, cholesterol, isofucosterol, sitosterol, accompanied by its saturated form, sitostanol, and the predominating stigmasterol. Again, one steroid ketone, tremulone (stigmasta-3,5-dien-7-one), and one biosynthetic precursor, 24-methylenecycloartanol, were also identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained diethyl ether extracts of hairy roots were fractionated chromatographically as described in Section 4.4 . Based on GC-MS analysis of the fraction of the free steroids, the compositions of these compounds were the same as described previously [ 27 ], i.e., the main sterols identified in this fraction were campesterol, cholesterol, isofucosterol, sitosterol, accompanied by its saturated form, sitostanol, and the predominating stigmasterol. Again, one steroid ketone, tremulone (stigmasta-3,5-dien-7-one), and one biosynthetic precursor, 24-methylenecycloartanol, were also identified.…”
Section: Resultsmentioning
confidence: 99%
“…However, the steroid biosynthesis reaction course, compared to jasmonic acid, was different in shoots, where a slight increase (11%) in total steroid content appeared seven days after foliar elicitor application, followed by a decrease (34%) after 14 days. Regarding a previous report on steroid metabolism modulation in C. officinalis hairy root cultures and plants exposed to cadmium stress [ 27 ], as well as metabolic changes in Taxus x media hairy roots triggered by jasmonic acid methyl ester [ 37 ], it might be concluded that sterol biosynthesis inhibition does not directly hamper plant growth induced by stress factors. On the contrary, in some cases, plant growth suppression can be inversely correlated with sterol content.…”
Section: Discussionmentioning
confidence: 99%
“…The main profile of sterols and the types of triterpenoid skeletons were the same, the main difference refers to the amount of triterpenoids, particularly triterpenoid acids. However, this feature (i.e., the prevalence of triterpenoid acids in C. monspeliensis ) cannot be considered universal, since the content of triterpenoids, classified as secondary (more aptly: specialized) metabolites, may differ significantly even between the plants of the same species growing in various habitats [ 31 , 32 ], and it can be modified under specific environmental conditions, e.g., biotic or abiotic stresses [ 34 , 35 ]. The study on C. ladanifer demonstrated a high intra-population variation of specialized metabolites, explained as a consequence of the interaction of the environmental variability of plant resources, genotypic differences among individuals, and herbivore or pathogen effects [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the metabolomic findings indicate that Cd boosted RA production via controlling amino acid metabolism but hindered tanshinone synthesis primarily by decreasing the GGPP concentration, with proline, POD, and CAT playing critical roles in Salvia miltiorrhiza ’s capacity to endure Cd stress ( Yuan et al., 2021 ). The reaction to Cd stress in Calendula officinalis plant roots appeared to be more influenced by metabolic changes, such as an increase in sterol production simultaneous to a decrease in the triterpenoid content of the plant roots and hairy root culture ( Rogowska et al., 2022 ).…”
Section: Various Approaches To Ameliorate Heavy Metal Stress In Medic...mentioning
confidence: 99%